DIAGNOSTIC ACCURACY OF NEUTROPHIL TO LYMPHOCYTE RATIO IN ACUTE APPENDICITIS WITH HISTOPATHOLOGY AS GOLD STANDARD - ISMAIL, Z; ZIA, R; ALI, ZM; FATIMA, B; BUSHRA, H; ZUBAIR, M; RAJPUT, IA; KHAN, NA (Biological and Clinical Sciences Research Journal, 2024)
Acute appendicitis is one of the most common surgical emergencies worldwide, requiring prompt and accurate diagnosis to prevent complications. In resource-constrained settings like Pakistan, reliance on advanced imaging modalities is often impractical. The Neutrophil-to-Lymphocyte Ratio (NLR) has emerged as a cost-effective and accessible biomarker for diagnosing acute appendicitis. Objective: This study aimed to evaluate the diagnostic accuracy of NLR in identifying acute appendicitis using histopathology as the gold standard. Methods: This cross-sectional study was conducted on 124 patients clinically suspected of having acute appendicitis at a tertiary care hospital. NLR values were calculated from routine complete blood counts, and histopathological examination was used to confirm the diagnosis. Diagnostic performance metrics, including sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and overall accuracy, were calculated. Stratified analyses were performed based on age, gender, and Modified Alvarado Scores. Results: The NLR cutoff of ≥3.5 demonstrated a sensitivity of 88.6%, specificity of 86.6%, PPV of 92.1%, NPV of 81.2%, and overall diagnostic accuracy of 87.9%. Diagnostic accuracy was higher in patients aged 46–70 years (92.8%) compared to those aged 18–45 years (83.8%). Male patients exhibited slightly better diagnostic accuracy (90.4%) than females (85.2%). Integration of NLR with the Modified Alvarado Score improved diagnostic precision, with accuracy reaching 88.2% in patients with scores >8.Conclusion: NLR is a reliable, cost-effective biomarker for diagnosing acute appendicitis, particularly in resource-limited settings. Its integration with clinical scoring systems can enhance diagnostic accuracy, reduce unnecessary appendectomies, and improve patient outcomes. Further research is needed to standardize NLR cutoff values and validate its application in broader clinical settings.